The Circuit of Culture Analysis of Black Women Representation on British Vogue Covers - Swastika, Gabriela Laras Dewi; Tanaka, Priscylia (Jurnal Audience: Jurnal Ilmu Komunikasi, 2025)
Media can shape the way the people see themselves, as well as the identity of a particular group collectively. In western countries where most of the population is dominated by white people such as Europe and North America, black people are included in a minority group that is vulnerable to discrimination and racism. The lack of opportunity for them to show their existence in the media has further obscured their identities and women are no exception. Representation in the media is no longer interpreted as representing a particular group’s identity but is used as a tool to fulfill media marketing strategies. This research aims to find out the forms of representation of black women in England that are mainly featured on two covers of British Vogue issued in August 2018 and February 2022. This research shows that the representation of black women featured on the cover of British Vogue’s August 2018 has represented black African American women, while the cover of the February 2022 has shown black African women. Both covers did not only attract the audiences in the UK but international audiences, moreover these covers have also indicated racial issues and feminism in the field of fashion. In this study, fashion magazine covers did not only show changes in fashion trends, but also the shifts in the representation of women’s identity and beauty standards. Keywords: representation; colorism; black women; British Vogue; circuit of culture.